2015
DOI: 10.2478/johr-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Polyamines Improve Mycorrhizal Development And Growth And Flowering Of Freesia hybrida

Abstract: An experiment was conducted in order to investigate the effects of exogenous polyamines (PAs) on the development of mycorrhizae in roots, nutrient uptake and vegetative and reproductive growth ofFreesia hybrida‘Golden Wave’. Corms of freesia were inoculated withRhizophagus intraradicesat sowing time and treated once a week by one of three PAs, putrescine (Put), spermidine or spermine, in concentrations of 0.05 and 0.1 mM each as foliar application or soil drench. Application of PAs, especially as soil drench, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…It might also be due to positively affected by organic manure because chemically, organic manures add an organic compound to the soil. These findings are in conformity with those of [30] in Freesia and [17] in Hydrangea.…”
Section: Plant Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…It might also be due to positively affected by organic manure because chemically, organic manures add an organic compound to the soil. These findings are in conformity with those of [30] in Freesia and [17] in Hydrangea.…”
Section: Plant Parameterssupporting
confidence: 91%
“…Gurung, et al [17] documented that the maximum stem thickness was observed in treatment T3 (Azotobacter + PSB + 80% RDF) in Hydrangea as compared to control. Also, Rezvanypour, et al [30] found that AMF (Arbuscular Mycorrhizal Fungi) inoculation caused significant increase in floral stem diameter for Freesia hybrida plants. The maximum stalk diameter of rose was recorded with Castor cake # 0.8 kg + Azotobacter # 1 ml + PSM # 1 ml + KSB # 1 ml / plant.…”
Section: Plant Parametersmentioning
confidence: 99%
“…Interestingly, while polyamines are detrimental to necrotrophic plant pathogens, the opposite appears to be true in the case of colonization by beneficial symbionts – particularly for mycorrhizal fungi. Polyamines increase in concentration during colonization of roots by AM (Sannazzaro et al ., 2007) and ECM fungi (Niemi et al ., 2006) while application of exogenous polyamines increases AM colonization (El Ghachtouli et al ., 1995; Wu & Zou, 2009; Rezvanypour et al ., 2015). Conversely, inhibition of polyamine formation reduces AM colonization (Wu et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This positive correlation between mycorrhizal colonization and PAs is validated by several studies. Based on their type and method of administration (soil drench or foliar application), PAs exerted their effectiveness on mycorrhizal (G. intraradices) development and concomitantly improved the quantity and quality of corm, and enhanced flower parameters in Freesia hybrida (Rezvanypour et al, 2015). The application of PAs in grape plants yielded beneficial effects on the infection rate, spore number, and hyphal growth of Gigaspora margarita, which are significantly reduced by the application of a PA biosynthetic inhibitor, methylglyoxal bis-guanylhydrazone (Yong et al, 2003).…”
Section: Impact Of Polyamines On Mycorrhizal Colonizationmentioning
confidence: 99%